Disney hits. Volume 1 [compact disc]. - Menzel, Idina; Weaver, Jason, 1979-; Atkinson, Rowan; Williams, Laura (Performer); Moore, Mandy, 1984-; Lauv (Musician), 1994-; Gaitán, Carolina, 1984-; Castillo, Mauro, 1978-; Adassa; Feliz, Rhenzy, 1997-; Guerrero, Diane, 1986-; Beatriz, Stephanie; et al. (Walt Disney Records, 2025)
A vibrant collection of fifteen classic songs from Disney's most beloved films. This album features fan favorites like Let It Go (Frozen), I Just Can't Wait to Be King (The Lion King), We Don't Talk About Bruno (Encanto), A Whole New World (Aladdin), and Part of Your World (The Little Mermaid). This compilation brings together timeless Disney magic in a beautifully curated package.